Moderating influence of product diversification on the international diversification-performance relationship : A meta-analysis - Arte, Pratik; Larimo, Jorma (Elsevier, 2021)
Numerous studies have examined the impact of international diversification on firm performance. However, the literature is characterised by inconsistent findings, suggesting the need for a quantitative review and synthesis of the hypothesised relationships. Using a sample of 263 effect sizes from 187 primary studies between 1974 and 2021, we conduct a meta-analysis to test the relationship between international diversification and firm performance, and the moderating effect of product diversification. The results of our meta-analysis indicate that the relationship between international diversification and firm performance is non-linear inverted U-shaped. Furthermore, we find that performance is higher in firms with low/related product diversity and lower in firms with high/unrelated product diversity, suggesting that the dual-diversification strategy is detrimental to firm performance. Although there is no significant difference in the performance of firms from advanced and emerging economies, the results highlight the importance of intangible assets for diversified firms.
Keywords: Firm performance; International diversification; Meta-analysis; Product diversification; fi=Markkinointi|en=Marketing|